ZnO/ZnS/Carbon Nanocomposite-Derived Sulfur-Doped carbon nanosheets using a layered nanoreactor: Towards advanced supercapacitor electrodes and devices - Yeganeh Ghotbi M.; Sikiru S.; Rajabi A.; Soleimani H.; Kou L.; Ansari M.N.M.; Ramachandaramurthy V.K. (Elsevier B.V., 2025)
Various approaches have been applied to increase the capacity of electric double layer capacitors (EDLC) by increasing the accessible surface area of the electrode material (mainly carbon) for electrolyte ions. One method is to make the active material particles smaller or use graphite-based carbon with less thickness. Another method involves doping carbon materials with some group III and V elements to create pseudo-capacitive properties. And finally, hybridization/combination of carbon with some metal compounds due to the inductive synergistic effect. Using the idea of layered nanoreactors, we prepared a ZnO/ZnS/S-doped carbon nanocomposite, i.e. producing a metal oxide/sulfide with a heteroatom-doped carbon material, simultaneously. ZnO/ZnS/carbon nanocomposite was acid washed to remove ZnO and obtain ZnS/C; ZnS/carbon nanocomposite was again acid washed to remove ZnS and obtain S-doped carbon material. ZnO/ZnS/S-doped carbon, ZnS/S-doped carbon nanocomposites and S-doped carbon materials showed the specific capacitance (Cs) values of 119, 1048 and 454F/g, respectively, when used as the active material in the three-electrode system. In addition, the S-doped carbon material showed a Cs value of 57F/g when used as the active material in the fabrication of a symmetric commercial-like supercapacitor device. ? 2024 Elsevier B.V.